Study on power matching strategy of PHEV based on fuzzy recognition of driving cycles - Limin NIU (The Japan Society of Mechanical Engineers, 2016)
In order to overcome adaptation deficiency of PHEV power assembly controlling strategy in complicated driving cycle, adaptive matching controlling strategy of driving-cycle fuzzy recognition was presented. The driving cycles of automobiles were classified in 3 types: rural cycle (RC), urban cycle (UC) and expressway cycle (EC). Based on information of automobile speed and acceleration, environment cycle is recognized via fuzzy inference, on those basis, adaptation of power matching model was realized. Moreover, simulation of power matching adaptive controlling strategy designed in this paper was conducted in ADVISOR. The designed controlling strategy and the electric-assisted controlling strategy were compared and analyzed. The results indicated that compared with electric-assisted controlling strategy, power-matching adaptive strategy of PHEV based on driving-cycle fuzzy recognition could further reduce energy consumption and exhaust emission, which proved that the newly designed controlling strategy could adapt driving cycles and enhance intellectualization of full vehicle.